1983
DOI: 10.1111/j.2042-7158.1983.tb04258.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of the human nail: permeation pattern for water and the homologous alcohols and differences with respect to the stratum corneum

Abstract: In order to develop a basic concept of the permeability of the human nail plate and thus create a better understanding of the toxic potentials and therapeutic possibilities of substances applied to the nail, avulsed cadaver nails have been placed in specially constructed diffusion chambers and their permeation by water and the n-alkanols through dodecanol, all in high aqueous dilution, has been investigated. The permeability coefficient of water is 16.5 X 10(-3) cm h-1 and that for methanol is 5.6 X 10(-3) cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 20 publications
3
46
0
2
Order By: Relevance
“…Despite the reported hydrophilic properties of the nail, hydrophobic compounds have been shown to diffuse into and through this barrier. For example Walters and coworkers reported that long chain alcohols permeate through the nail via a lipidic pathway (9,13). Subsequent work failed to find any evidence of a distinctive pathway for the transport of hydrophobic chemicals (8).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite the reported hydrophilic properties of the nail, hydrophobic compounds have been shown to diffuse into and through this barrier. For example Walters and coworkers reported that long chain alcohols permeate through the nail via a lipidic pathway (9,13). Subsequent work failed to find any evidence of a distinctive pathway for the transport of hydrophobic chemicals (8).…”
Section: Introductionmentioning
confidence: 94%
“…The structure of human nail has been likened to a hydrophilic gel membrane (7)(8)(9). It is considered to consist of three layers; the dorsal, intermediate and ventral.…”
Section: Introductionmentioning
confidence: 99%
“…In general, differences between nail and stratum corneum lipids occur mainly in the fractions of ceramides, free sterols, free fatty acids and triglycerides, the first three of them being components which are regarded to be of crucial importance for the epidermal permeability barrier [2]. Interestingly, both plantar stratum corneum [17] and nails show low barrier properties, the nail plate being considered to have a transcorneal water loss 10-to 1,000-fold higher than the stratum corneum [21], although the relative proportions of ceramides, free sterols (plantar stratum corneum) and free fatty acids (nail) are relatively high. This underlines that conclusions on the permeability barrier cannot be reduced to quantitative changes of lipid class proportions alone.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the increase in alcohol skin permeability coefficients with carbon chain length, there was an initial decline in alcohol permeability coefficients with increase in carbon chain length (fig. 9) [52], prompting the authors to postulate that ‘the hydrated nail plate behaves like a hydrogel of high ionic strength to the polar and semipolar alcohols…' with a ‘parallel lipid pathway' for the more permeable n-decanol and n-dodecanol [60]. In later work, they concluded that ‘solvents which tend to promote diffusion through the skin horny layer have little promise as accelerants of nail plate permeability' [61].…”
Section: Gordon Flynn - Experimental Verification and Development Of mentioning
confidence: 99%